Rancang Bangun Antena Mikrostrip dengan Metamaterial CSRR untuk Penerima TV Digital - Mariani, Dina; Safarudin, Yanuar Mahfudz (Jurnal Sustainable: Jurnal Hasil Penelitian dan Industri Terapan, 2018)
Digital television technology has more benefit than analog television, for example several TV channel may included in one frequency channel. The changing from analog to digital televisions system require more innovative antenna parameter such as working frequency, bandwidth, return loss, VSWR, and gain. In other hand, the size of the antenna must be minimalized, so it can be integrated inside digital television. This research used metamaterial element of Complementary Split Ring Resonator (CSSR) method with negative permittivity that manufactured in the patch and Double Pole Ground Plane in the ground side. The antenna ad 478-694 operating frequency. Antenna design and simulation using CST (Computer Simulation Technology) Microwave Studio 2012. The result show that return-loss value < -10 dB, and VSWR â¤ 2 at 478-625 MHz range of frequency. Te value of gain is 3.27 dBi, it has 147 MHz bandwidth, and omnidirectional radiation pattern.